MyD88 and beyond: a perspective on MyD88-targeted therapeutic approach for modulation of host immunity - Saikh, Kamal U. (Immunol Res, 2021)
ABSTRACT: The continuous emergence of infectious pathogens along with antimicrobial resistance creates a need for an alternative approach to treat infectious diseases. Targeting host factor(s) which are critically involved in immune signaling pathways for modulation of host immunity offers to treat a broad range of infectious diseases. Upon pathogen-associated ligands binding to the Toll-like/ IL-1R family, and other cellular receptors, followed by recruitment of intracellular signaling adaptor proteins, primarily MyD88, trigger the innate immune responses. But activation of host innate immunity strongly depends on the correct function of MyD88 which is tightly regulated. Dysregulation of MyD88 may cause an imbalance that culminates to a wide range of inflammation-associated syndromes and diseases. Furthermore, recent reports also describe that MyD88 upregulation with many viral infections is linked to decreased antiviral type I IFN response, and MyD88-deficient mice showed an increase in survivability. These reports suggest that MyD88 is also negatively involved via MyD88-independent pathways of immune signaling for antiviral type I IFN response. Because of its expanding role in controlling host immune signaling pathways, MyD88 has been recognized as a potential drug target in a broader drug discovery paradigm. Targeting BB-loop of MyD88, small molecule inhibitors were designed by structure-based approach which by blocking TIR–TIR domain homo-dimerization have shown promising therapeutic efficacy in attenuating MyD88-mediated inflammatory impact, and increased antiviral type I IFN response in experimental mouse model of diseases. In this review, we highlight the reports on MyD88-linked immune response and MyD88-targeted therapeutic approach with underlying mechanisms for controlling inflammation and antiviral type I IFN response. HIGHLIGHTS: • Host innate immunity is activated upon PAMPs binding to PRRs followed by immune signaling through TIR domain–containing adaptor proteins mainly MyD88. • Structure-based approach led to develop small-molecule inhibitors which block TIR domain homodimerization of MyD88 and showed therapeutic efficacy in limiting severe inflammation-associated impact in mice. • Therapeutic intervention of MyD88 also showed an increase in antiviral effect with strong type I IFN signaling linked to increased phosphorylation of IRFs via MyD88–independent pathway. • MyD88 inhibitors might be potentially useful as a small-molecule therapeutics for modulation of host immunity against inflammatory diseases and antiviral therapy. • However, prior clinical use of more in-depth efforts should be focused for suitability of the approach in deploying to complex diseases including COPD and COVID-19 in limiting inflammation-associated syndrome to infection.